The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.9734/jamb/2021/v21i830374
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Examination of Used Towels from Female and Male Hostel of Federal University of Lafia

Abstract: Bath towels have the ability to retain microbes, moist and warm environment offers microbes a favorable place to grow and survive. These microbes can be transmitted through direct contact with our hands and other inanimate objects within the environment. This study aimed at examining bacterial contamination of used towels. Used towels from male and female hostels at Federal University of Lafia, were assessed to determine their bacterial concentration. A total of sixteen (16) used towels were sampled, eight tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…DISCUSSION The bacteriological examination of students' bath towels showed that the towels were colonized by major pathogenic microorganisms that are regularly recorded in many human diseases with counts ranging from 3.4 x 10 4 to 2.9 x 10 8 cfu/cm 3 . Similar observations have been reported in body towels [15]. Although, much lower bacterial loads have been recorded from other varieties of textiles in the healthcare environment [4].…”
Section: Resultssupporting
confidence: 83%
“…DISCUSSION The bacteriological examination of students' bath towels showed that the towels were colonized by major pathogenic microorganisms that are regularly recorded in many human diseases with counts ranging from 3.4 x 10 4 to 2.9 x 10 8 cfu/cm 3 . Similar observations have been reported in body towels [15]. Although, much lower bacterial loads have been recorded from other varieties of textiles in the healthcare environment [4].…”
Section: Resultssupporting
confidence: 83%